2018
DOI: 10.1002/eqe.3073
|View full text |Cite
|
Sign up to set email alerts
|

Seismic performance analysis of BRBs and gussets in a full‐scale 2‐story BRB‐RCF specimen

Abstract: Summary The implementation of buckling‐restrained braces (BRBs) for new reinforced concrete frame (RCF) constructions is limited. This study investigates the seismic forces and stability in the BRBs and gussets of a 2‐story full‐scale RCF specimen by using Abaqus models and a newly proposed stability evaluation method. The hybrid and cyclic loading test results are accurately predicted by the Abaqus analyses. Existing methods for computing the gusset interface forces for steel buildings from both the brace and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…To this end, the study relied on publicly available data from past experimental tests on BRBFs conducted at a full-scale and large-scale. A total of 12 relevant experimental campaigns, published between 2004 and 2018 [[2], [3], [4], [5], [6], [7], [8], [9], [10], [11], [12], [13], [14], [15], [16], [17], [18], [19], [20], [21], [22], [23]], were compiled to investigate the values that the YLR take in very detailed BRBF specimens. Table 1 summarizes the information regarding the 12 experimental studies.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, the study relied on publicly available data from past experimental tests on BRBFs conducted at a full-scale and large-scale. A total of 12 relevant experimental campaigns, published between 2004 and 2018 [[2], [3], [4], [5], [6], [7], [8], [9], [10], [11], [12], [13], [14], [15], [16], [17], [18], [19], [20], [21], [22], [23]], were compiled to investigate the values that the YLR take in very detailed BRBF specimens. Table 1 summarizes the information regarding the 12 experimental studies.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…[22], Tsai et al. [23]One-bay, two-story new reinforced concrete (RC) frame with BRBs, with diagonal bracing configuration2-story 1-bay BRB-RC frameFull-scaleHybrid test + Cyclic loading testWelded3473, 35866025, 59800.58, 0.60…”
Section: Datamentioning
confidence: 99%
“…where actions can be respectively obtained by using the generalized uniform force method [43] and the improved equivalent strut model [30]. In addition, it should be noted that the extra moment, Mub, resulting from regular shape of gusset plates should be taken into account to check the weld size on the gusset-to-beam interfaces [31].…”
Section: Identification Of Members For the Brb-becft Framementioning
confidence: 99%
“…On the other hand, it should be noted that the connection between BRBs and boundary members is of crucial importance due to the fact that axial tension and compression of the BRB need to be effectively delivered to frames through gusset plates to resist earthquake action. Previous system-level experiments [11,30,31] have shown that gusset plates were subjected not only to BRB axial force, but also to frame action resulting from opening and closing of beam-to-column joint. This behavior was found to cause that gusset plates became more susceptible to weld fracture near the gusset tips or buckling deformation prior to failure of the BRBs, thus impairing the seismic performance of the dual system.…”
Section: Introductionmentioning
confidence: 99%
“…Global stability is another main consideration when examining BRBF behaviour. Evidence following the 2011 Tōhoku Earthquake [11] and from several full frame tests have shown BRBFs to perform well [12][13][14][15][16][17]. However, the complexity of BRB behaviour makes it difficult to verify frame stability for all configurations and sizes.…”
Section: Introductionmentioning
confidence: 99%